2006
DOI: 10.1111/j.1469-8137.2006.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Multivesicular compartments proliferate in susceptible and resistant MLA12‐barley leaves in response to infection by the biotrophic powdery mildew fungus

Abstract: Summary• There is growing evidence that multivesicular bodies and cell wall-associated paramural bodies participate in the enhanced vesicle trafficking induced by pathogen attack.• Here, we performed transmission electron microscopy in combination with cytochemical localization of H 2 O 2 to investigate multivesicular compartments during establishment of compatible interaction in susceptible barley ( Hordeum vulgare ) and during hypersensitive response in resistant MLA12 -barley infected by the barley powdery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
129
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(145 citation statements)
references
References 74 publications
5
129
0
1
Order By: Relevance
“…GFP-PEN1 was additionally located in the apparent interior of cell wall containing papillae [70]. Because electron micrographs have shown the presence of membranebound vesicles within papilla [76][77][78], this hints to unusual trafficking events and extrusion of vesicles in the paramural space, some of which might become trapped in the papillary cell wall scaffold. The directed movement of GFP-VAMP722 vesicles to pathogen portals and a pen phenocopy seen in VAMP721 +/À VAMP722 À/À mutant plants is consistent with the hypothesis that plasma membrane-resident PEN1 syntaxin acts through the formation of heterooligomeric SNARE complexes, enabling focal secretion of vesicle cargo at fungal entry sites [69].…”
Section: Opinionmentioning
confidence: 99%
“…GFP-PEN1 was additionally located in the apparent interior of cell wall containing papillae [70]. Because electron micrographs have shown the presence of membranebound vesicles within papilla [76][77][78], this hints to unusual trafficking events and extrusion of vesicles in the paramural space, some of which might become trapped in the papillary cell wall scaffold. The directed movement of GFP-VAMP722 vesicles to pathogen portals and a pen phenocopy seen in VAMP721 +/À VAMP722 À/À mutant plants is consistent with the hypothesis that plasma membrane-resident PEN1 syntaxin acts through the formation of heterooligomeric SNARE complexes, enabling focal secretion of vesicle cargo at fungal entry sites [69].…”
Section: Opinionmentioning
confidence: 99%
“…PMBs were discerned by transmission electron microscopy several decades ago, and subsequent morphological studies revealed that PMBs are frequently observed in plant tissues in which exocytosis and endocytosis occur actively (Marchant and Robards, 1968;Wang et al, 2005;An et al, 2006aAn et al, , 2006b. Some studies also proposed that PMBs are involved in the internalization of cell wall components and plasma membrane proteins (Cox and Juniper, 1973;Herman and Lamb, 1992).…”
Section: Subcellular Effects Of the Vps9a Mutationmentioning
confidence: 99%
“…In addition, succinate, malate, and fumarate are part of the citric acid cycle in mitochondria and the glyoxylic acid cycle in peroxisomes. Thus, another possibility for the changes in the accumulation of these metabolites following elicitation is that they are a consequence of exocytosis events that are known to occur in plant cell-pathogen interactions (Brown et al, 1998) and may involve peroxisomes that move toward and accumulate at the site of infection (Scheel, 1998;Lipka et al, 2005;An et al, 2006;Hardham et al, 2008).…”
Section: Metabolic Changes In the Transgenic Cell Linesmentioning
confidence: 99%